Analysis Of The Influence Of Electronic Word Of Mouth Communication (E-Wom) and Pricing Strategy On Purchasing Decisions In Richeese Factor Restaurants - Fauzi Apriliana; Rakhmat; Erliza (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2024)
This study aims to determine the effect of word of mouth electronic communication and pricing strategies on purchasing decisions at Richeese Factory Restaurant. The population in this study were all consumers of Richeese Factory Kemang Pratama. The method used in this study is qualitative, namely by obtaining research results from collecting respondent data. The sampling technique used a questionnaire and the data analysis technique used multiple linear regression analysis, t test, f test and the coefficient of determination using SPSS software version 26. The results of this study indicate that based on the analysis of multiple linear regression coefficients, it can be concluded that there is a significant relationship between electronic word of mouth communication and price strategy on purchasing decisions at Richeese Factory Restaurant where if word of mouth electronic communication (X1) and strategy (X2) experience an increase one unit, the purchase decision (Y) will increase.